Use of Sterile Materials and Soaking Time For Banana (Musa Spp) Explant - Nora Augustien (Sean Institute, 2024)
NaOCl is often used in various sterilization techniques with various concentrations and soaking times. In addition to NaOCL which is used for explant sterilization, 70% alcohol is also often used for the explant sterilization process. Usually mushrooms or fungi will die if exposed to a 70% alcohol solution. The aim of the study was to determine the method of sterilization with NaOCl concentration followed by immersion in alcohol on the acquisition of sterile explants of kepok banana plant. The research was conducted at the Biotechnology Laboratory, Faculty of Agriculture, UPN Veteran, East Java. The research design used a non-factorial Completely Randomized Design (CRD), the treatment consisted of 6 sterilization treatments namely (S1), (S2), (S3), (S4), (S5), (S6). The results showed that there was no effect between the concentration of NaOCl sterilization and the duration of immersion in alcohol on the percentage of live explants and the percentage of contaminated explants, and the sterilization method used can produce live and sterile explants with an average yield of below 50%, but in treatment (S6) 25% NaOCl + 70% alcohol for 30 minutes is able to produce 30% live and sterile explants. Various sterilization methods used gave good results on the percentage of stagnant explants.